Deciphering in-store-online switching in multi-channel retailing context: Role of affective commitment to purchase situation. (November 2021) - Jebarajakirthy, Charles; Das, Manish; Shah, Dhara; Shankar, Amit
Abstract: Customers today make a trade-off between online and offline channels to purchase fashion items. The purpose of this research is to examine whether affective commitment to a purchase situation impacts consumers' channel choice (online store or in-store) for fashion purchases. Two between-subjects' experimental studies were designed to test hypotheses. Binary logistics regression, chi-square test, two-way ANOVA and PROCESS Macro were used to test hypotheses. The findings of study 1 showed that in a high affectively committed purchase situations, consumers prefer to purchase fashion items in-store whereas in low affectively committed purchase situations, they prefer online. Further, hedonic benefits mediate the association between affective commitment and channel selection. Study 2 re-confirmed the findings of study 1 and showed that customer channel choice varies between high and low affective commitment levels depending on customer innovation seeking tendency. This study enriches the multi-channel literature and provide several implications to multi-channel fashion retailers. Highlights: Channel choice behaviour in multi-channel retailing is a challenge for fashion retailers. Using two experimental studies, we examine whether affective commitment to a purchase situation affects consumers' channel choice. In high affectively committed purchase situations, consumers prefer purchasing in-store whereas in low affectively committed situations, they prefer online. Customers' channel choice (i.e. online vs offline) varies between high and low affective commitment levels depending on customer innovation seeking tendency.